Undergraduate research and the academic librarian case studies and best practices - Hensley, Merinda Kaye; Davis-Kahl, Stephanie (Association of College and Research Libraries, a division of the American Library Association, 2017)
"Undergraduate research is often conflated with standard end-of-semester research papers, featuring APA style bibliographies and a certain number of sources. But in fact, undergraduate research is one of several high-impact educational practices identified by George Kuh and the Association of American Colleges & Universities, and is increasingly seen as a vital part of the undergraduate experience. Research helps students connect the dots between their interests, general education courses, writing requirements, and major coursework, and increases learning, retention, enrollment in graduate education, and engagement in future work. In 25 chapters featuring 60 expert contributors, Undergraduate Research and the Academic Librarian examines how the structures that undergird undergraduate research, such as the library, can become part of the core infrastructure of the undergraduate experience. It explores the strategic new services and cross-departmental collaborations academic libraries are creating to support research: publishing services, such as institutional repositories and undergraduate research journals; data services; copyright services; poster printing and design; specialized space; digital scholarship services; awards; and much more. These programs can be from any discipline, can be interdisciplinary, can be any high-impact format, and can reflect upon an institution's own history, traditions, and tensions. As higher education becomes more competitive--for dollars, for students, for grant money, for resources in general--institutions will need to increase their development of programs that provide the experiential and deep learning, and increased engagement, that research provides. The scholarly and extracurricular experiences of college are increasingly becoming a major part of marketing college education. Beyond the one-shot, beyond course-integrated instruction, Undergraduate Research and the Academic Librarian is a detailed guide to how librarians can help students go beyond a foundation of information literacy toward advanced research and information management skills"--provided by publisher